WEBVTT
00:00:02.640 --> 00:00:08.570
Given that four 𝑥 cubed minus two 𝑦 cubed plus 18 equals zero, find d𝑦 d𝑥.
00:00:09.490 --> 00:00:12.540
So what we’re gonna do here is actually differentiate our function.
00:00:12.940 --> 00:00:15.530
And to do that, what we’re gonna use is implicit differentiation.
00:00:16.330 --> 00:00:23.340
Now the first stage of differentiating implicitly is actually to differentiate each term in our function with respect to 𝑥.
00:00:24.270 --> 00:00:31.220
Now if we’re gonna differentiate each term with respect to 𝑥, this is gonna be very straightforward for the terms that just include 𝑥 or just a numerical value.
00:00:31.620 --> 00:00:34.790
However, I’m just gonna show you it’s slightly different when we’re dealing with the one which is in 𝑦.
00:00:35.920 --> 00:00:38.090
Well, our first term is just gonna be 12𝑥 squared.
00:00:38.940 --> 00:00:45.760
Then I’m gonna leave our second term just as minus 𝑑 d𝑥 of two 𝑦 cubed cause what I wanna do is deal with this separately.
00:00:46.640 --> 00:00:54.250
And then, we get plus zero cause if you differentiate 18, you just get zero and then equals zero because again if you differentiate zero, you just get zero.
00:00:54.810 --> 00:00:58.860
Okay great, so now let’s differentiate our 𝑦 term with respect to 𝑥.
00:00:59.040 --> 00:01:04.510
So we can now explain how we’re gonna differentiate our term two 𝑦 cubed with respect to 𝑥.
00:01:05.380 --> 00:01:21.300
So first of all, if we have a function that’s in 𝑦 or a term that’s in 𝑦 and we want to differentiate it with respect to 𝑥, we can actually apply the chain rule and say that it’s gonna be equal to the same function differentiated with respect to 𝑦 multiplied by d𝑦 d𝑥.
00:01:22.450 --> 00:01:25.170
So now what we’re gonna do is actually apply it to our term in 𝑦.
00:01:25.560 --> 00:01:30.720
So we we’re gonna have the derivative of two 𝑦 cubed with respect to 𝑥.
00:01:30.920 --> 00:01:33.560
It’s gonna be equal to six 𝑦 squared.
00:01:33.970 --> 00:01:43.950
And that’s because if we actually differentiate two 𝑦 cubed with respect to 𝑦, we get six 𝑦 squared because we multiplied the exponent three by the coefficient two gives us six.
00:01:44.140 --> 00:01:47.170
And then we reduce the exponent by one gives us 𝑦 squared.
00:01:48.400 --> 00:01:50.550
And then, this is multiplied by d𝑦 d𝑥.
00:01:50.740 --> 00:01:56.950
So great, we now know that derivative with respect to 𝑥 of two 𝑦 cubed is equal to six 𝑦 squared d𝑦 d𝑥.
00:01:57.730 --> 00:02:00.690
So now what we’re gonna do is move on to the second stage of our implicit differentiation.
00:02:00.690 --> 00:02:06.020
And what we do now is we’re actually gonna rearrange to make d𝑦 d𝑥 the subject because this is what we’re looking for.
00:02:06.790 --> 00:02:09.900
So the first thing we’re gonna do is actually subtract 12𝑥 squared from each side.
00:02:10.220 --> 00:02:14.550
So we get negative six 𝑦 squared d𝑦 d𝑥 is equal to negative 12𝑥 squared.
00:02:15.570 --> 00:02:21.250
And then next, what I do is actually divide through by negative six 𝑦 squared to leave d𝑦 d𝑥 on its own.
00:02:21.250 --> 00:02:25.410
So we get d𝑦 d𝑥 is equal to negative 12𝑥 squared over negative six 𝑦 squared.
00:02:26.300 --> 00:02:29.720
So then, we actually divide the numerator and denominator by negative six.
00:02:29.930 --> 00:02:33.600
So we’re left with two 𝑥 squared over 𝑦 squared.
00:02:34.420 --> 00:02:44.620
So therefore, we can say that given that four 𝑥 cubed minus two 𝑦 cubed plus 18 equals zero, then, d𝑦 d𝑥 is gonna be equal to two 𝑥 squared over 𝑦 squared.